PRELIMINARY ORAL PROBIOTICS BACTERIAL PROFILE IN NEONATAL AND PEDIATRICS AND ITS CLINICAL EVALUATION - SHETTY, GAMANA B.; K. R, TALLURI RAMESHWARI; K., SUMANA (International Journal of Current Pharmaceutical Research, 2022)
Probiotics are live bacteria that are consumed or administered to the body to provide health advantages. They are in yoghurt and other fermented food consumer, as well as dietary supplements and cosmetics too. After birth, the mouth of the infant is richly colonized immediately. The different probiotic microorganisms present in infants are Bifidobacterium, Streptococcus salivarius, Streptococcus albicans, Lactobacillus crispatus, Lactobacillus gasseri. Some of these can exhibit some powerful anti-inflammatory capabilities. For the novel application of probiotics in pediatric nutrition, there is a new concept in the composition of the microbiota. In probiotic food, it contains healthy microorganisms, which helps in the safe gut association with lymphoid tissue in infants. Traditionally, probiotics have been associated with gut health, and most clinical interest has been focused on their use for the prevention or treatment of gastrointestinal infections and diseases; however, during the last decade, several investigators have also suggested the use of probiotics for oral health purposes. The aim of this review is to examine the potential mechanisms of probiotic bacteria in the oral cavity and summarize the observed effects of probiotics with respect to oral health. The research focuses on probiotic lactobacilli and its genera that are most used in various probiotic products. Due to this reason, the idea of the usage of probiotics is leading the way to new therapeutic perspectives.